2015
DOI: 10.1080/15685551.2015.1041085
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel drug-loaded polymer, poly(lactic acid-co-aminomethyl benzimidazole)

Abstract: 2015): Synthesis and characterization of a novel drug-loaded polymer, poly(lactic acid-co-aminomethyl benzimidazole), Designed Monomers and Polymers, Using aminomethyl benzimidazole (AMB) as a model of benzimidazole-type drugs, a potential biodegradable drug-loaded polymer poly(lactic acid-co-aminomethyl benzimidazole) (PLAAMB) is synthesized as designed via direct melt polycondensation starting from D,L-lactic acid (LA). When the molar feed ratio LA/AMB is 40/1, the optimal synthetic conditions, including cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The polymer/solvent miscibility has been shown to have a direct bearing on the final fiber diameter and morphology. For instance, fibers made from PLA in dichloromethane have been shown to have a broader range of fiber diameters [32][33][34]. Results reported by Wei et al [35] on the electrospinning of Polyvinylidene fluoride (PVdF) nanofibers showed that the concentrations of solvent Methyl ethyl ketone (MEK) in DMF greatly influenced the dimensions and morphology of PVdF nanofibers.…”
Section: Introductionmentioning
confidence: 91%
“…The polymer/solvent miscibility has been shown to have a direct bearing on the final fiber diameter and morphology. For instance, fibers made from PLA in dichloromethane have been shown to have a broader range of fiber diameters [32][33][34]. Results reported by Wei et al [35] on the electrospinning of Polyvinylidene fluoride (PVdF) nanofibers showed that the concentrations of solvent Methyl ethyl ketone (MEK) in DMF greatly influenced the dimensions and morphology of PVdF nanofibers.…”
Section: Introductionmentioning
confidence: 91%
“…Biodegradable polymer microspheres have been extensively investigated as potential carriers for drugs, cosmetic products, delivery systems, and for diagnostic purposes because of their biocompatibility, biodegradability, stability, and sustained-release properties. , Among the most studied materials for encapsulation are derivatives of poly­( d , l -lactide), poly­( d , l -lactide- co -glycolide) (PLGA), and poly-ε-caprolactones, and the most widespread mechanism for encapsulation with them is the total enfold of the molecule of interest by the polymeric thin film to generate a spherical microparticle.…”
Section: Introductionmentioning
confidence: 99%